2012
DOI: 10.1002/jor.22102
|View full text |Cite
|
Sign up to set email alerts
|

Neural‐differentiated mesenchymal stem cells incorporated into muscle stuffed vein scaffold forms a stable living nerve conduit

Abstract: Autologous nerve grafts to bridge nerve gaps have donor site morbidity and possible neuroma formation resulting in development of various methods of bridging nerve gaps without using autologous nerve grafts. We have fabricated an acellular muscle stuffed vein seeded with differentiated mesenchymal stem cells (MSCs) as a substitute for nerve autografts. Human vein and muscle were both decellularized by liquid nitrogen immersion with subsequent hydrolysis in hydrochloric acid. Human MSCs were subjected to a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Undifferentiated MSCs displayed a flat fibroblast-like morphology: a spindle shape with short processes whereas differentiated cells appear in star-shape with elongated processes. Flow cytometry analysis also showed that human MSCs isolated from human bone marrow in our lab have tested positive for mesenchymal cell surface markers such as CD 90, CD105, CD 10, CD 29, and CD 44 but negative for hematopoietic cell markers, CD34 and CD 45 [15]. To examine the efficiency of MSC differentiation as an alternative source of SCs, the cells were subjected to a series of treatments with a reducing agent, retinoic acid, and a combination of trophic factors.…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…Undifferentiated MSCs displayed a flat fibroblast-like morphology: a spindle shape with short processes whereas differentiated cells appear in star-shape with elongated processes. Flow cytometry analysis also showed that human MSCs isolated from human bone marrow in our lab have tested positive for mesenchymal cell surface markers such as CD 90, CD105, CD 10, CD 29, and CD 44 but negative for hematopoietic cell markers, CD34 and CD 45 [15]. To examine the efficiency of MSC differentiation as an alternative source of SCs, the cells were subjected to a series of treatments with a reducing agent, retinoic acid, and a combination of trophic factors.…”
mentioning
confidence: 70%
“…Previous studies have shown that PLGA-coated collagen is superior to vein graft in nerve regeneration [20,21]. Furthermore, the ability of human MSCs to differentiate into neuronal cells and facilitate the neuronal growth that has been studied previously [15,22]. Thus, we undertook the study to evaluate the survival and propagation of human nMSC in collagen-coated PLGA tube.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations